Preservation and Restoration of Sphincter Function in Patients with Rectal Cancer - Rudolf Schiessel; Harald R Rosen (Canadian Journal of Gastroenterology)
Radical resection of rectal cancer is the standard treatment for curing this disease. Half of these tumours are located in the rectosigmoid region or the upper third of the rectum and are, therefore, easily resectable with preservation of the sphincter muscles, thus guaranteeing acceptable continence in most patients. However, tumours that originate in the lower parts of the rectum have been accompanied with the need for an abdominoperineal resection and the threat of a permanent colostomy. In the past 20 years, sphincter-saving surgery has become increasingly common in the treatment of tumours of the middle and low rectum due to the knowledge of tumour growth, the use of stapling devices, and the knowledge of the physiology of the pelvic floor and the sphincter muscles, respectively. Recent surgical techniques of resection of the ’ultralow’ rectum (intersphincteric resection) and the reconstruction by coloanal anastomosis are reviewed. Functional problems following ultralow resections are emphasized, as well as the possibility of sphincter restoration after abdominoperineal resection by use of dynamic graciloplasty. Taking all surgical options into account, a permanent colostomy for rectal cancer can be avoided in most curatively and electively operated patients.